A Feminist Approach to the Images of Women in That Long Silence and Palace of Desire (Qasr Al-Shawq): A Comparative Study - Kawan, Ghassan Dhahed; Karmarkar, P R (South Asian Journal of Social Sciences and Humanities, 2024)
This paper investigates the depiction of women in Shashi Deshpande’s That Long Silence and Naguib Mahfouz’s Palace of Desire (Qasr Al-Shawq) according to the feminist approach. The study seeks to compare and contrast the way these two novels, which are considered among reputable 20th century fiction, represent female characters and their struggles for asserting their individualities in two types of male-dominated societies. That is to say, Shashi Deshpande, the Indian authoress of That Long Silence fathoms the struggles of women in a traditional Indian society. In this novel, she mirrors the great challenges that women face in such a patriarchal system. Therefore, this research traces the heroines’ experience highlighting how the novelist has tackled misogynism and biased societal prospects. On the other hand, Mahfouz’s Palace of Desire sheds light on the stereotyped images of women and feminists attempts to free women within the changing political and societal setting of Egypt then. Aida’s personality represents the ambitious woman who reconciles with her desires and does her best to assert herself in a male-dominated society despite all the social constraints trying to limit her aspirations. In this comparative study between the two concerned novels, the researcher seeks to reveal the similarities and differences in the representations of women in two different cultural backgrounds. So, the paper examines how each of these two novelists criticizes the patriarchal structures and advocates feminism in his/ her society exposing the ways through which gender roles and societal norms are presented. The study shows a deep understanding of feminist literary criticism by highlighting the cultural influence of the two societies in which women’s sufferings are revealed. So, the findings of the research offer new insights into the gender roles, misogynism, stereotyped images of women, old traditions and patriarchal systems in literature.